Involvement of ionomic metabolism of both the cerebrospinal fluid and the spinal cord in the analgesic efficacy of matrine in rats - Jin-Lu Huang; Chen-Yue Tang; Yao Fu; Li-Li Wan; Jie Li; Xi-Peng Sun; Jia-Lu Hu; Yue-Yi Zhang; Li-Ying Qu; Miao-Jia Fu; Yuan-Yuan Zhang; Le Ma; et al. (Pharmaceutical Biology)
Context Matrine has antinociceptive properties, and spinal cord ionomic changes are involved in bone cancer pain.Objective To investigate the relationship between ionomic metabolism in cerebrospinal fluid (CSF) and spinal cord and matrine’s analgesic efficacy.Materials and methods The antinociceptive effects of matrine were identified in rats via intraperitoneal (i.p.) injection using the tail-immersion and formalin tests. Pharmacodynamic parameters for matrine against formalin-induced pain were calculated with nonlinear regression analysis. Inductively coupled plasma mass spectrometry (ICP-MS) technology was utilized to detect contents of the ionome in CSF and spinal cord. Variations in ionomic metabolism in different treated groups were examined using Pearson’s correlation coefficients and principal component analysis (PCA).Results In the tail-immersion test, matrine significantly prolonged tail-flick latency in rats. Matrine also dose-dependently yielded analgesia against formalin-induced biphasic pain, with an onset at around 10 min post-injection and a duration of 100 min. The ED50 and Emax values were 19.01 mg/kg and 71.86% for phase I and 40.30 mg/kg and 81.51% for phase II, respectively. Pearson’s correlation coefficient study and PCA revealed significant reprogramming of ionomic metabolism in the CSF and the spinal cord in the NM (normal saline + matrine), NF (normal saline + formalin), and FM (formalin + matrine) groups, compared to the NN (normal saline + normal saline) group.Discussion and conclusions These findings broaden the known analgesic spectrum of matrine and provide novel insights into the involvement of ionomic metabolism in its analgesic efficacy.